Effect of intellectual enrichment on AD biomarker trajectories: Longitudinal imaging study. (22nd March 2016) - Vemuri, Prashanthi; Lesnick, Timothy G.; Przybelski, Scott A.; Knopman, David S.; Machulda, Mary; Lowe, Val J.; Mielke, Michelle M.; Roberts, Rosebud O.; Gunter, Jeffrey L.; Senjem, Matthew L.; Geda, Yonas E.; Rocca, Walter A.; et al.
Abstract : Objective: To investigate the effect of age, sex, APOE4 genotype, and lifestyle enrichment (education/occupation, midlife cognitive activity, and midlife physical activity) on Alzheimer disease (AD) biomarker trajectories using longitudinal imaging data (brain β-amyloid load via Pittsburgh compound B PET and neurodegeneration via 18 fluorodeoxyglucose (FDG) PET and structural MRI) in an elderly population without dementia. Methods: In the population-based longitudinal Mayo Clinic Study of Aging, we studied 393 participants without dementia (340 clinically normal, 53 mild cognitive impairment; 70 years and older) who had cognitive and physical activity measures and at least 2 visits with imaging biomarkers. We dichotomized participants into high (≥14 years) and low (<14 years) education levels using the median. For the entire cohort and the 2 education strata, we built linear mixed models to investigate the effect of the predictors on each of the biomarker outcomes. Results: Age was associated with amyloid and neurodegeneration trajectories; APOE4 status appears to influence only the amyloid and FDG trajectories but not hippocampal volume trajectory. In the high-education stratum, high midlife cognitive activity was associated with lower amyloid deposition in APOE4 carriers. APOE4 status was associated with lower FDG uptake in the entire cohort and in participants with lower education but not the high-education cohort. Conclusions: There were minimal effects of lifestyle enrichment on AD biomarker trajectories (specifically rates). Lifetime intellectual enrichment (high education, high midlife cognitive activity) is associated with lower amyloid in APOE4 carriers. High education is protective from the APOE4 effect on FDG metabolism. Differing education levels may explain the conflicting results seen in the literature.